2008
DOI: 10.1063/1.3046582
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiency and reduced spectral shift of green light-emitting-diode epitaxial structure with prestrained growth

Abstract: The enhanced emission efficiency and reduced spectral shifts of a green InGaN/GaN quantum-well (QW) light-emitting-diode epitaxial structure by using the prestrained growth technique when compared with a control sample of the same emission spectrum with conventional growth are demonstrated. By adding an ∼7%-indium InGaN/GaN QW to the structure before the growth of designated emitting high-indium QWs, the growth temperature of the emitting QWs can be raised by 30 °C while keeping about the same emission wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Both will affect the formation of S-K islands. For example, Huang et al [66] found enhanced emission efficiency for green InGaN/GaN QW LEDs when a pre-strained buried layer was added. Park et al [67] used surface roughening to enhance PS in thin InGaN layers grown on GaN.…”
Section: Stranski-krastanov Growthmentioning
confidence: 99%
“…Both will affect the formation of S-K islands. For example, Huang et al [66] found enhanced emission efficiency for green InGaN/GaN QW LEDs when a pre-strained buried layer was added. Park et al [67] used surface roughening to enhance PS in thin InGaN layers grown on GaN.…”
Section: Stranski-krastanov Growthmentioning
confidence: 99%
“…We believe that the existence of V-pits in the active layer improves the emission characteristics. To fabricate highefficiency InGaN-based LEDs on a sapphire substrate, an InGaN/GaN superlattice (SL) beneath MQWs is often used [11][12][13]. Some mechanisms are reported in which a higher hole injection efficiency and formation of a potential barrier at dislocations are achieved, as well as a reduction in the strain in MQWs, preventing the propagation of dislocations or point defects and decreasing electron mobility [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although blue LEDs are already commercially available, it is still difficult to fabricate long wavelength LEDs [4][5][6] because of the large (11%) lattice mismatch between InN and GaN and the strong piezoelectric field-induced quantum-confined Stark effect bGuoq J( $IGPEG LG!O[ nuqobGq (QCSE) [7,8] induced by the high strain due to lattice mismatch. Extensive researches have recently focused on adjusting the strain in the quantum well layer [9][10][11][12][13] to improve the device efficiency and change the emission wavelength. Nanhui et al [9,10] introduced a strain-relief underlying layer to reduce the strain in the InGaN well layers and enhance the output power.…”
Section: Introductionmentioning
confidence: 99%
“…Nanhui et al [9,10] introduced a strain-relief underlying layer to reduce the strain in the InGaN well layers and enhance the output power. Professor Yang's team [11][12][13] used the prestrained growth technique to elongate the emission wavelength and enhance emission efficiency.…”
Section: Introductionmentioning
confidence: 99%